HUBUNGAN PERSEPSI PEMILIH PEMULA TERHADAP INFORMASI DI (INSTAGRAM) DENGAN PENGAMBILAN KEPUTUSAN PILPRES - Winy Rivany; Nurmina Nurmina (Universitas Negeri Padang, 2019)
This research is about the political phenomena that exist in Indonesia.According to the survey results that most of the population in Indonesia are in the age range of 15-22 years, so this age in the political category is the beginner voter.So that political parties and candidates make teenagers the main target.This type of research is quantitative correlational. The research subjects were 150 beginner voters consisting of ages 17 to 21 years. The sampling method uses purposive sampling technique. Data collection is done by using a scale of perception of information on instagram and decision making. Data analysis using Product Moment Correlation Coefficient. The results of the study show that there is a significant relationship between perceptions of information on the instagram and decision-making on the beginning voters in the city of Padang. Penelitian mengenai fenomena politik yang ada di Indonesia saat ini. Menurut hasil survey di dapatkan bahwa kebanyaka